ANALYSIS OF MATERNAL RISK FACTORS IN THE DEVELOPMENT OF ADVERSE PERINATAL OUTCOMES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The aim of the study was to investigate the prevalence of major maternal risk factors in two clinical groups of women and to assess their potential impact on the course of pregnancy and delivery. A comparative analysis of obstetric, gynecological, and somatic history was performed in 60 women divided into two groups. The study revealed that women in Group II significantly more often had chronic somatic diseases, infectious foci, anemia of pregnancy, and a family history of allergic diseases, indicating a less favorable background for gestation and childbirth.